5/7 x x +9/7x x=2/5
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: x-4/5=3/7
=>x=3/7+4/5=43/35
b: x+3/7=4/5
=>x=4/5-3/7=13/35
c: 19/20-x=8/5-3/4
=>19/20-x=32/20-15/20=17/20
=>x=2/20=1/10
d: =>4/5*x=2/21
=>x=2/21:4/5=5/42
e: =>x:7/9=6/8
=>x=6/8*7/9=3/4*7/9=21/36=7/12
f: =>x/6=2/3-1/3=1/3
=>x=2
![](https://rs.olm.vn/images/avt/0.png?1311)
a: x-4/5=3/7
=>x=3/7+4/5=43/35
b: x+3/7=4/5
=>x=4/5-3/7=13/35
c: 19/20-x=8/5-3/4
=>19/20-x=32/20-15/20=17/20
=>x=2/20=1/10
d: =>4/5*x=11/21
=>x=55/84
e: =>x=6/8*7/9=42/72=7/12
f: =>x/6=2/3-1/3=1/3
=>x=2
![](https://rs.olm.vn/images/avt/0.png?1311)
\(1,\\ a,=7x^3-49x^2+21x\\ b,=x^2-x-42\\ c,=x^2-16x+64\\ d,=9x^2+12x+4\\ e,=x^2-16-25+10x-x^2=10x-41\\ 2,\\ a,\Rightarrow2\left(x-7\right)=19\\ \Rightarrow x-7=\dfrac{19}{2}\Rightarrow x=\dfrac{33}{2}\\ b,\Rightarrow4x^2-20x+25-4x^2+3x-2x=50\\ \Rightarrow-19x=25\Rightarrow x=-\dfrac{25}{19}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
1/ Suy ra: -35 + 7x - 2x + 20 = 15
5x - 15 = 15
5x = 30
x = 6
2/ Suy ra: 4x - 20 - 3x - 21 = -19
x - 41 = -19
x = 22
3/ Suy ra: 8 - 4x + 3x - 15 = 14
-7 -x = 14
x = -7 -14
x = -21
4/ Suy ra: 7x - 63 - 30 + 5x = -6 + 11x
7x + 5x - 11x = -6 +63 + 30
x = 87
5/ Suy ra: -21x +35 + 14x - 28 = 28
-21x + 14x = 28 +28 - 35
-7x = 21
x= -3
6/ Suy ra: 20 - 5x + 7x - 14 = -2
2x = -8
x = -4
7/ Suy ra: 4x +15 -5x = 7
-x = -8
x = 8
8/ Suy ra: 5x - 35 +30 -10x = 20
-5x - 5 = 20
-5x = 25
x = -5
9/ Suy ra: 35 - 7x + 5x - 10 = 15
-7x + 5x = 15 +10 - 35
-2x = -10
x = 5
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có: \(\frac{3}{3.5}+\frac{3}{5.7}+\frac{3}{7.9}+...+\frac{3}{x.\left(x+2\right)}=\frac{8}{7}\)
\(\Leftrightarrow3\left(\frac{1}{3.5}+\frac{1}{5.7}+\frac{1}{7.9}+...+\frac{1}{x.\left(x+2\right)}\right)=\frac{8}{7}\)
\(\Leftrightarrow3.\left(\frac{2}{3.5}+\frac{2}{5.7}+\frac{2}{7.9}+...+\frac{2}{x\left(x+2\right)}\right).\frac{1}{2}=\frac{8}{7}\)
\(\Leftrightarrow\frac{3}{2}.\left(\frac{1}{3}-\frac{1}{5}+\frac{1}{5}-\frac{1}{7}+...+\frac{1}{x}-\frac{1}{x+2}\right)=\frac{8}{7}\)
\(\Leftrightarrow\frac{3}{2}.\left(\frac{1}{3}-\frac{1}{x+2}\right)=\frac{8}{7}\)
\(\Leftrightarrow\frac{1}{3}-\frac{1}{x+2}=\frac{8}{7}:\frac{3}{2}=\frac{8}{7}.\frac{2}{3}=\frac{16}{21}\)
\(\Leftrightarrow\frac{1}{x+2}=\frac{1}{3}-\frac{16}{21}=\frac{-3}{7}\)
\(\Leftrightarrow\frac{-3}{-3\left(x+2\right)}=\frac{-3}{7}\)
\(\Leftrightarrow-3\left(x+2\right)=7\)
\(\Leftrightarrow x+2=\frac{7}{-3}\)
\(\Leftrightarrow x=\frac{7}{-3}-2=\frac{-13}{3}\)
Vậy \(x=\frac{-13}{3}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
`a,4x-10=0 `
`<=> 4x=10`
`<=>x=10/4`
`<=>x=5/2`
`b, 7-3x=9-x `
`<=>-3x+x=9-7`
`<=>-2x=2`
`<=>x=-1`
`c, 2x-(3-5x) = 4(x+3)`
`<=>2x-3+5x=4x+12`
`<=>2x+5x-4x=12+3`
`<=>3x=15`
`<=>x=5`
`d, 5-(6-x)=4(3-2x) `
`<=>5-6+x=12-8x`
`<=>x+8x=12-5+6`
`<=>9x=13`
`<=>x=13/9`
`e, 4(x+3)=-7x+17 `
`<=>4x+12=-7x+17`
`<=>4x+7x=17-12`
`<=>11x=5`
`<=>x=5/11`
`f, 5(x-3) - 4=2(x-1)+7`
`<=>5x-15-4=2x-2+7`
`<=>5x-2x=15+4-2+7`
`<=>3x=24`
`<=>x=8`
`g, 5(x-3)-4=2(x-1)+7 `
`<=>5x-15-4=2x-2+7`
`<=>5x-2x=15+4-2+7`
`<=>3x=24`
`<=>x=8`
`h,4(3x-2)-3(x-4)=7x+20`
`<=>12x-8-3x+12=7x+20`
`<=>12x-3x-7x=20+8+12`
`<=>2x=40`
`<=>x=20`
![](https://rs.olm.vn/images/avt/0.png?1311)
\(a,-5.\left(-x+7\right)-3.\left(-x-5\right)=-4.\left(12-x\right)+48\)
\(5x-35-3x+15=-48+4x+48\)
\(2x-10=4x\)
\(2x-4x=10\)
\(-2x=10\)
\(x=-5\)
\(b,\left(-x-7\right)-5.\left(-x-3\right)=12.\left(3-x\right)\)
\(-x-7+5x+15=36-12x\)
\(4x+8=36-12x\)
\(4x+12x=36-8\)
\(16x=28\)
\(x=1,75\)
các câu còn lại tương tự nha
![](https://rs.olm.vn/images/avt/0.png?1311)
a) = (x+3).(x-3)^2-(x-3)(x+3)^2
=(x^2-9)(x-3)-(x^2-9)(x+3)
=(x^2-9)(x-3-x-3)
=-6(x^2-9)
các câu còn lại tương tự
\(a,\left(x+3\right)\left(x^2-3x+9\right)-\left(x-3\right)\left(x^2+3x+9\right)\)
\(=x^3+3-\left(x^3-3\right)\)
\(=x^3+3-x^3+3\)
\(=6\)
\(b,\left(x-5\right)\left(x^2+5x+25\right)-\left(x+5\right)\left(x^2-5x+25\right)\)
\(=x^3-5^3-x^3-5^3\)
\(=-125-125\)
\(=-250\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a ) \(-5\times\left(-x+7\right)-3\times\left(-x-5\right)=-4\times\left(12-x\right)+48\)
\(\Leftrightarrow5x-35+3x+15=-48+4x+48\)
\(\Leftrightarrow5x-3x+4x=35-15-48+48\)
\(\Leftrightarrow2x=20\)
\(\Leftrightarrow x=10\)
b ) \(-2\times\left(15-3x\right)-4\times\left(-7x+8\right)=-5-9\times\left(-2x+1\right)\)
\(\Leftrightarrow-30+6x-28x-32=-5+18x-9\)
\(\Leftrightarrow6x-28x-18x=30+32-5-9\)
\(\Leftrightarrow-40x=48\)
\(\Leftrightarrow x=-1.2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x+\dfrac{3}{4}=9\)
\(x=\dfrac{9}{1}-\dfrac{3}{4}\)
\(x=\dfrac{36-3}{4}=\dfrac{33}{4}\)
\(\dfrac{1}{7}:x=\dfrac{2}{7}\)
\(x=\dfrac{2}{7}:\dfrac{1}{7}\)
\(x=\dfrac{2}{7}.\dfrac{7}{1}=\dfrac{14}{7}=2\)
( 5/7 + 9/7 ) x X = 2/5
2 x X = 2/5
X = 2/5 : 1/2
X = 1/5
5/7 x X + 9/7 x X = 2/5
[ 5/7 + 9/7 ] x X = 2/5
12/7 x X = 2/5
X = 2/5 : 12/7
X = 7/30